Experiencia, aborto y maternidad en las católicas feministas - Gudiño Bessone, Pablo (Nómadas. Critical Journal of Social and Juridical Science, 2012)
The Catholic Church’s opposition to feminist demands for the decriminalization of abortion, allows to visualize the disputes and tensions that are taking place within the field of Catholicism over the redefinition of traditional values that represent women. In their demands for the gender rights, the Latin-American Network of Catholics for a Free Choise -a current of catholic women whom also vindicate themselves as feminists- conceives access to safe contraception and the legalization of abortion as an example of freedom of conscience. In this essay we analyze the normative postulates of the ecclesiastic hierarchy with regard to the sexuality and the reproduction, at the same time as we propose to study the political-discursive narrative of this collective of women and their arguments in favour of the right to decide on the own body.
Keywords: Catholic Church; feminists; abortion; experience; motherhood.